A Comparative Histological Study Between Injection and Oral Administration of New Cadmium Aminonitril Complex (CAC) in Layer Chickens to Control or Treat E. coli Infection and Their Counts in Digestive Tract - Areej, A.M.; Rawaa, A.M.; Abood, Dhyaa Ab.; Al-Hammed, Sanaa A.A. (International Journal of Poultry Science, 2012)
Cadmium of alpha-aminonitrile Complex (CAC) is a [Di nitrato-bis {(p-methyl anilino) phenyl acetonitrile} Cadmium (II)]. (2)Hydrate, [Cd(HL)2(NO3)2].2H2O tested against E. coli (sensitivity test) in vitro showed inhibitory zone of 12 mm. 90 healthy layer chickens (Lohman brown), of 49 weeks age, weighing 1800-2200 gm, have been used in this study. They are divided into ten main groups, five groups for each experiment (T1, T2, T3, T4 and T5), each main group divided into 3 subgroups. All birds were housed in an optimal poultry field. In experiment 1, the CAC was injected subcutaneously into the layer chicken at different levels, (T2 0.25%, T3 0.50% and T4 1.0%). After five days E. coli was orally administrated by drinking water for the treatments (T2, T3, T4 and T5) at titer of 8500 x 106 cells/ml (highly pathogenic) as causative agent of Salpingitis and Ovaritis. Uninjected uninfected T1 was used as control. In experiment 2, E. coli was orally administrated to T2, T3, T4 and T5 by drinking water at titer of 8500 x 106 cells/ml (highly pathogenic) as causative agent of Salpingitis and Ovaritis. After two days the CAC has been used to treat the layer chickens at different levels, (T2 0.25%, T3 0.50% and T4 1.0%) by mixing it with the diet. Uninfected untreated T1 0.0% was used as a control. T5 was important to identify the infection and the count of E. coli infection and its count in infected uninjected chickens. The results after four months showed a resistance against E. coli infection by the treated chicken in both experiment. The results were confirmed by measuring the residual concentration of Cd (II) ions in liver and egg samples of treated chicken by using the atomic absorption. The histopathological results revealed that histological structure is normal in all specimens of (liver, kidney, muscle, oviduct and cerebellum), which is associated with the control (T1). The specimens of liver and kidney of T5 at 8500 x 106 cells/ml of E. coli concentration showed pathological changes. Liver showed amyloidosis, congestion of central vein with RBC, increased in coffer cells. Kidneys represent congestion in interstitial tissue and distended of bowman’s space. The liver and egg specimens of treated chicken showed that they were free from any Cd (II) ion residues. E. coli counts in both experiments showed decreasing in E. coli count and increasing of CAC concentrations. The obtained results refer to the safety use of CAC as a synthetic chemical prophylactic or treating agent against E. coli during the production period of layers, in addition to its inexpensive cost.